The evolutionary dynamics and epidemiological history of hepatitis C virus genotype 6, including unique strains from the Li community of Hainan Island, China. Issue 1 (16th February 2022) - Xu, Ru; Aranday-Cortes, Elihu; Leitch, E Carol McWilliam; Hughes, Joseph; Singer, Joshua B; Sreenu, Vattipally; Tong, Lily; da Silva Filipe, Ana; Bamford, Connor G G; Rong, Xia; Huang, Jieting; Wang, Min; et al.
Abstract: Hepatitis C virus (HCV) is a highly diverse pathogen that frequently establishes a chronic long-term infection, but the origins and drivers of HCV diversity in the human population remain unclear. Previously unidentified strains of HCV genotype 6 (gt6) were recently discovered in chronically infected individuals of the Li ethnic group living in Baisha County, Hainan Island, China. The Li community, who were early settlers on Hainan Island, has a distinct host genetic background and cultural identity compared to other ethnic groups on the island and mainland China. In this report, we generated 33 whole virus genome sequences to conduct a comprehensive molecular epidemiological analysis of these novel gt6 strains in the context of gt6 isolates present in Southeast Asia. With the exception of one gt6a isolate, the Li gt6 sequences formed three novel clades from two lineages which constituted 3 newly assigned gt6 subtypes and 30 unassigned strains. Using Bayesian inference methods, we dated the most recent common ancestor for all available gt6 whole virus genome sequences to approximately 2767 bce (95 per cent highest posterior density (HPD) intervals, 3670–1397 bce ), which is far earlier than previous estimates. The substitution rate was 1.20 × 10 −4 substitutions/site/year (s/s/y), and this rate varied across the genome regions, from 1.02 × 10 −5 s/s/y in the 5'untranslated region (UTR) region to 3.07 × 10 −4 s/s/y in E2. Thus, our study on an isolated ethnic minority group within a small geographical area of Hainan Island has substantially increased the known diversity of HCV gt6, already acknowledged as the most diverse HCV genotype. The extant HCV gt6 sequences from this study were probably transmitted to the Li through at least three independent events dating perhaps from around 4, 000 years ago. This analysis describes deeper insight into basic aspects of HCV gt6 molecular evolution including the extensive diversity of gt6 sequences in the isolated Li ethnic group.